Demographic and clinical factors associated with immune reconstitution in HIV/HBV co‐infected and HIV mono‐infected patients: a retrospective cohort study. Issue 11 (25th December 2020) - Jiang, TY; Hou, JH; Su, B; Zhang, T; Yang, Y; Liu, ZY; Wang, W; Guo, CP; Dai, LL; Sun, LJ; Wu, H
Abstract : Objectives: To describe the clinical characteristics and factors associated with CD4 T‐cell count and CD4/CD8 ratio restoration in HIV mono‐infected and HIV/HBV co‐infected individuals, and to explore liver and renal functional changes in both groups. Methods: A retrospective cohort study was performed including 356 HIV/HBV co‐infected and 716 HIV mono‐infected participants who initiated antiretroviral therapy (ART) during 2013–2017 in Beijing Youan Hospital, China. Demographic and clinical characteristics were compared between the two groups, using χ 2 and Mann–Whitney non‐parametric tests. Bivariate and multivariate Cox regression models were used to test their association. Results: Baseline HIV viral load and ART regimen were found to be significantly associated with CD4 T‐cell restoration among HIV‐infected participants, whereas baseline HIV viral load was the only significant factor associated with CD4 T‐cell restoration in HIV/HBV co‐infected participants. The final model showed that baseline HIV viral load and ART regimen were significantly associated with CD4/CD8 ratio restoration among HIV‐infected participants, while baseline HIV viral load was the significant factor. Liver and renal functions were similar at the endpoint ( P > 0.05). Conclusions: Baseline HIV viral load count was found to be the key factor affecting immune restoration in both HIV and HIV/HBV individuals. Future multi‐wave prospective studies are needed to clarify the potential biological mechanism.